A study of nonlinear fractional-order biochemical reaction model and numerical simulations - Radhakrishnan, Bheeman; Chandru, Paramasivam; Nieto, Juan J. (Nonlinear Analysis: Modelling and Control, 2024)
This article depicts an approximate solution of systems of nonlinear fractional biochemical reactions for the Michaelis–Menten enzyme kinetic model arising from the enzymatic reaction process. This present work is concerned with fundamental enzyme kinetics, utilised to assess the efficacy of powerful mathematical approaches such as the homotopy perturbation method (HPM), homotopy analysis method (HAM), and homotopy analysis transform method (HATM) to get the approximate solutions of the biochemical reaction model with time-fractional derivatives. The Caputo-type fractional derivatives are explored. The proposed method is implemented to formulate a fractional differential biochemical reaction model to obtain approximate results subject to various settings of the fractional parameters with statistical validation at different stages. The comparison results reveal the complexity of the enzyme process and obtain approximate solutions to the nonlinear fractional differential biochemical reaction model.
Keywords: fractional differential equation; nonlinear biochemical reaction model; Caputo fractional derivative; homotopy perturbation method; homotopy analysis method; homotopy analysis transform method